Value of Information Sharing on Bullwhip Effect with Risk-averse Consideration - Shi, Xiutian (Institutional Knowledge at Singapore Management University, 2011)
We study the bullwhip effect with risk-averse consideration in this paper. The literature, given assumption that the decision makers are risk neutral, on information sharing and bullwhip effect in the business press is proliferation, while modern supply chains are becoming increasingly complex and sensitive to uncertainties. In the field of finance, a significant operational approach, meanvariance analysis, is widely used to deal with risk aversion. Based on these research, we start with developing a model of two-stage supply chain consisting two risk averse members, one retailer and one manufacturer. This problem is similar to the risk-averse agent's optimal inventory problem. Then, we prove the risk averse decision maker's utility function, which combines the expected and variance of profit in the coming period, is unimodal in the order-up-to level. With that, we extend the proposition by considering two cases differentiated by information sharing. Moreover, our analysis and numerical examples provide further illustration of our work.